Integrated Proteotranscriptomics of Human Myometrium in Labor Landscape Reveals the Increased Molecular Associated With Inflammation Under Hypoxia Stress - Chen, Lina; Wang, Lele; Luo, Yihong; Huang, Qian; Ji, Kaiyuan; Bao, Junjie; Liu, Huishu (Frontiers in Immunology, 2021)
During labor, a variety of coordinated physiological and biochemical events cause the myometrium to transition from a quiescent to contractile state; the molecular mechanisms responsible for this transition, however, remain unclear. To better understand this transition at a molecular level, the global transcriptome and proteome of human myometrial samples in labor and those not in labor were investigated through RNA sequencing (RNA-seq) and quantitative liquid chromatography–tandem mass spectrometry (LC-MS/MS) via data-independent acquisition (DIA) and parallel reaction monitoring (PRM) methods. Furthermore, an integrated proteotranscriptomic analysis was performed to explore biological processes and pathway alterations during labor; this analysis identified 1,626 differentially expressed mRNAs (1,101 upregulated, 525 downregulated) and 135 differentially expressed proteins (97 upregulated, 38 downregulated) in myometrium between nonlabor and in labor groups. The comprehensive results of these analyses showed that the upregulated mRNAs and proteins increased inflammation under hypoxia stress in the myometrium under labor, and related proteins and cytokines were validated by PRM and Luminex assays. Our study confirmed the biological process of inflammation and hypoxia in laboring myometrium at the transcriptome and proteome levels and provided recourse to discover new molecular and biological changes during labor.